Faculty of Pharmacy excellence appreciation ceremony with the dean of the faculty / Mohd Nadzri Mohd Najib and Nurul Alyaa binti Ibrahim - Mohd Najib, Mohd Nadzri; Ibrahim, Nurul Alyaa (Faculty of Pharmacy, 2024)
On May 15, 2024, the Faculty of Pharmacy at UiTM Bertam held a remarkable Excellence Appreciation Ceremony, organised by the Society of Pharmacy Students (SOPHYS). This event aimed to celebrate academic excellence among students and to boost their motivation for the upcoming final examination for this semester.